The anxiety & phobia workbook - Bourne, Edmund J. (New Harbinger Publications, Inc., 2020)
Celebrating 30 years as a classic in its field, The Anxiety and Phobia Workbook is an unparalleled, essential resource for people struggling with anxiety and phobias. This fully revised and updated seventh edition of the best-seller offers powerful, step-by-step treatment strategies for panic disorders, agoraphobia, generalized anxiety disorder, obsessive-compulsive disorder (OCD), post-traumatic stress disorder (PTSD), worry, and fear. Readers will also find new information on relapse prevention after successful treatment, and updates on medication, marijuana derivatives, exposure, nutrition,